Ni–Cu alloy nanoparticles loaded on various metal oxides acting as efficient catalysts for photocatalytic H2 evolution1. Issue 56 (19th June 2015) - Yamada, Yusuke; Shikano, Shinya; Fukuzumi, Shunichi
<x xml:space="preserve">Abstract</x> Catalysis of Ni–Cu alloy nanoparticles loaded on various metal oxides for photocatalytic H2 evolution depends on preparation methods and supports.